Batch Adsorption of Maxilon Red GRL from Aqueous Solution by Natural Sugarcane Stalks Powder. (1st August 2013) - El-Sayed, Gamal Owes; Mohammed, Talaat Younis; Salama, Ashraf Abd-Allah
Abstract : Sugarcane stalks powder was tested for its efficiency of removing a textile dye Maxilon Red GRL from aqueous solution. Different parameters affecting dye removal efficiency were studied. These parameters include contact time, initial dye concentration, adsorbent dose, ionic strength, pH, and temperature. Langmuir and Freundlich isotherm models were applied to the equilibrium data. The data fitted well with the Langmuir isotherm (R 2 > 0.99 ). The maximum monolayer adsorption capacity (Q 0 ) was found to be 20.96 mg/g at an initial pH of 7.2. The temperature variation study showed that dye adsorption is exothermic and spontaneous with increased randomness at the solid solution interface. The results indicated that sugarcane stalks could be an alternative for more costly adsorbents used for dye removal. The kinetic of the adsorption process followed the pseudo second-order kinetics model.